Ekspresi Spiritualitas dalam Musik Liturgi Gereja Pantekosta - Happy Blessing Melody Sanggor; Mimy Astuty Pulukadang; Laode Karlan; Trubus Semiaji; Rahmawati Ohi (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This study was motivated by the role of liturgical music as the primary medium of spiritual expression in Pentecostal worship, which is characterised by expressiveness and participation. The purpose of this study was to analyse the presentation of liturgical music and examine how it shapes and represents the spiritual expression of the congregation in the worship services of the Indonesian Bethel Church (GBI) Light Corner in Gorontalo City. The research uses a qualitative approach with a descriptive-interpretative design. Data were obtained through participatory observation, in-depth interviews with worship leaders and congregants, and audio-visual documentation. Data analysis was conducted thematically with reference to musicology, liturgical theology, and cultural studies perspectives. The results of the study show that liturgical music at GBI Light Corner is presented in a structured yet flexible manner, combining contemporary music with conscious liturgical planning. Music serves as a medium for creating a sacred atmosphere, binding the structure of worship, and as the main means of expressing the spirituality of the congregation both personally and communally. These findings indicate that liturgical music not only reflects the spirituality of the congregation but also actively shapes the experience of faith in the context of the local Pentecostal Church. This research has implications for the development of contextual, theological, and reflective liturgical music practices in church life.